Method for extracting germanium from lignite
Through alkali catalyzing hydrothermal decomposition of lignite, the problems of germanium waste and environmental pollution during germanium extraction are solved, the germanium recovery rate and organic matter production are improved, and efficient and environmentally friendly germanium extraction and organic matter utilization are achieved.
Patent Information
- Application Number
- CN202411355423.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art has problems of germanium waste, environmental pollution and unutilization of high-value organic matter in the germanium extraction process in lignite, and the process is long, there are many types of agents, and the incomplete extraction of high-value chlorosulfur acid and rare metals is not recovered.
The method of alkali catalyzed hydrothermal decomposition of lignite is used to hydrothermal decompose the humic acid precursor to produce secondary humic acid, and the primary humic acid, secondary humic acid and germanium complexed thereto are extracted at the same time, through alkali The liquid and polymerization inhibitor undergo hydrothermal reaction, followed by solid-liquid separation and acidic distillation to obtain germanium tetrachloride.
It improves germanium recovery and high-value organic compounds production, shortens processes, reduces drug use and environmental pollution, and enhances economic benefits and resource utilization.
Smart Images

Figure CN119242961A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal element extraction, in particular to a method for extracting germanium from lignite. Background Art
[0002] At present, the main method for extracting germanium from lignite is to pre-enrich germanium by combustion. In this method, germanium-containing lignite is burned in a weakly reducing atmosphere, so that the germanium in the coal volatilizes into the smoke in the form of volatile germanium monoxide (GeO) or germanium sulfide (GeS), and then the smoke containing germanium (i.e., crude germanium concentrate) is obtained by collecting dust in a dust collector. Then, according to the germanium content of the crude germanium concentrate, it is selected whether to perform secondary enrichment, and finally the germanium-containing smoke ash is subjected to chlorination distillation to obtain crude germanium tetrachloride. Since chlorination requires a large amount of high-concentration hydrochloric acid, the consumption of hydrochloric acid is large, and a large amount of waste acid liquid and low-grade germanium-containing waste residue will be generated, which is difficult to handle, not only causing a waste of germanium, but also affecting the environment. In addition, the use of combustion method for pre-enrichment of germanium has a high water content, low calorific value, low combustion efficiency, and great environmental pollution due to the high water content of lignite. More importantly, lignite has a low degree of metamorphism and generally contains humic acid (including brown humic acid and fulvic acid), especially fulvic acid, which can be used as foliar fertilizer, pesticide, medical and health products, cosmetics, environmental protection treatment agent, etc., and has high value. Burning will burn these high-value organic matter in vain, only generating heat energy in the process, and causing environmental pollution.
[0003] Prior art: A Chinese patent with publication number CN114262794B discloses a method for comprehensively extracting valuable components such as rare elements and organic matter from lignite. The method mainly comprises the following steps: (1) crushing the raw coal; (2) oxidative pretreatment to initially release the rare metals such as germanium, gallium, and rare earth contained in the lignite; (3) heating and alkali treatment to deeply release the rare metals in the lignite and dissolve the alkali-soluble organic matter in the lignite; (4) controlled potential acid treatment to precipitate the acid-insoluble organic matter from the alkali treatment solution and promote the decomposition of the rare metals complexed by the organic matter; and (5) wastewater treatment and circulation, neutralization and circulation of the residual acid solution after the rare metals are extracted in the treatment process and the residual alkali solution in the alkali treatment process.
[0004] This technology not only extracts rare metals from lignite, but also realizes the productization of residual organic matter in lignite (actually brown-black humic acid), with little residual solids and easy to turn into building materials. Most of the residual acid and alkali solutions in the treatment process can be processed within the process and recycled. The process has the advantages of less environmental pollution, high economic benefits, and high comprehensive utilization rate of valuable components. However, this method also has some shortcomings: 1) the process is relatively long and requires three solid-liquid separations; 2) there are many types of reagents used, and there are two heating steps (pre-oxidation and heated alkaline dissolution), except for hydrogen peroxide oxidation pretreatment (no heating required); 3) the high-value humic acid in lignite is not recovered; 4) no method is given for the recovery of rare metals in the first and third stage dissolution solutions; 5) there is no data or theoretical support for the desorption effect of the complexing agents (catechol, N-hydroxyphthalimide, tartaric acid, hydroxamic acid) added during the mono-acid treatment on the rare metals complexed on humic acid and the solubility of the complexes formed by these substances with rare metals in acidic solutions.
[0005] Since humic acid and lignin-like substances in lignite contain a large number of oxygen-containing functional groups (such as carboxyl, phenolic hydroxyl, methoxy, etc.), they are easily complexed with germanium in coal, so most of the germanium in coal is affinity with the above two substances. Although the conventional lignite alkali extraction method can extract the native humic acid and the germanium complexed with it in the coal at the same time, there is still a considerable amount of germanium affinity with lignin-like substances. Due to the large molecular weight of lignin, the proportion of hydrophilic functional groups is relatively small, and the hydrophilicity is weak, so it cannot be extracted. Summary of the invention
[0006] The object of the present invention is to provide a method for extracting germanium from lignite, which adopts a method of alkaline-catalyzed hydrothermal decomposition of lignite to hydrothermally decompose humic acid precursors (lignin-like substances) present in large quantities in lignite to produce secondary humic acid, and simultaneously extract primary humic acid, secondary humic acid and germanium complexed with the two.
[0007] To solve the above problems, the present invention adopts the following technical solutions:
[0008] The present invention provides a method for extracting germanium from lignite, comprising the following steps:
[0009] Step 1: Mix the germanium-containing lignite with alkali solution, and add an inhibitor to carry out a hydrothermal decomposition reaction to obtain a slurry.
[0010] Step 2, separating the slurry obtained in step 1 into solid and liquid to obtain filter residue A and filtrate A; wherein the filter residue A is washed with water for multiple times, and the washing liquid is mixed into the filtrate A.
[0011] Step 3, using hydrochloric acid to adjust the pH value of the filtrate A to be less than or equal to 1, and distilling the filtrate A slurry while stirring, and the distilled germanium tetrachloride is received and sealed with high-purity water.
[0012] Step 4, the filtrate A slurry after the distillation is first allowed to stand and cool and stratify, and then solid-liquid separation is performed to obtain filter residue B and filtrate B; wherein the filter residue B is washed with water for multiple times, and the washing liquid is incorporated into the filtrate B.
[0013] The beneficial effect of the present invention is that the present invention provides a method for extracting germanium from lignite, which adopts a method of hydrothermal decomposition of lignite by alkali catalysis, hydrothermal decomposition of humic acid precursors (lignin-like substances) present in large quantities in lignite, produces secondary humic acid, and simultaneously extracts primary humic acid, secondary humic acid and germanium complexed with the two. The hydrothermal decomposition reaction of lignin-like substances can promote the generation of small molecular weight substances, so this method can also increase the yield of humic acid in lignite. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Shown is a flow chart of the method for extracting germanium from lignite of the present invention.
[0015] Figure 2 Shown are the molecular formulas of the three basic structural units of lignin.
[0016] Figure 3 Shown is a schematic diagram of the cleavage of the β-O-4 bond in the lignin model compound to generate a syringyl derivative.
[0017] Figure 4 Shown is a schematic diagram of the cleavage of the α-O-4 bond and the formation of the guaiacol derivative.
[0018] Figure 5 Shown is C α Schematic diagram of the condensation reaction of -Ar.
[0019] Figure 6 Shown is a diagram showing the experimental results of the temperature change conditions of the present invention.
[0020] Figure 7 Shown is a graph showing the experimental results of the reaction time variation conditions of the present invention.
[0021] Figure 8 Shown is a graph showing the experimental results of the alkali solution concentration change conditions of the present invention.
[0022] Fig. 9 Shown is a graph showing the results of the distillation time variation condition experiment of the present invention.
[0023] Fig.10 Shown is a graph showing the results of an experiment on varying the amount of phenol added according to the present invention.
[0024] Fig.11 Shown is a graph showing the experimental results of the liquid-to-solid ratio variation conditions of the present invention. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below in conjunction with specific embodiments. The following description is only used to illustrate the technical solution of the present invention but not to limit it. The experimental methods used in the embodiments are conventional methods unless otherwise specified. The materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.
[0026] The present invention provides a method for extracting germanium from lignite, wherein the raw material processed by the method is coal containing at least germanium, humic acid, and lignin-like substances; the method is particularly suitable for germanium-containing lignite. Figure 1 The flowchart of the method for extracting germanium from lignite of the present invention is shown in FIG. 1 , and the method comprises the following steps:
[0027] Step 1: Mix the germanium-containing lignite with alkali solution, and add an inhibitor to carry out a hydrothermal decomposition reaction to obtain a slurry.
[0028] Specifically, alkali solution and germanium-containing lignite are taken at a liquid-solid mass ratio of 4:1-8:1, and a hydrothermal decomposition reaction is carried out in a high-temperature and high-pressure reactor (acid and alkali resistant liner). The alkali solution can be selected from sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, potassium carbonate solution, sodium sulfide solution, or any combination thereof. Preferably, sodium hydroxide solution is used with a concentration of 0.1mol / L-0.4mol / L. The inhibitor is phenol or boric acid, preferably phenol, and the addition amount is 9%-11% of the mass of the germanium-containing lignite. The hydrothermal decomposition temperature is 180°C-220°C, and the reaction time is 2-4 hours.
[0029] Step 2, separating the slurry obtained in step 1 into solid and liquid to obtain filter residue A and filtrate A; wherein the filter residue A is washed with water for multiple times, and the washing liquid is mixed into the filtrate A.
[0030] Step 3, using hydrochloric acid to adjust the pH value of filtrate A to less than or equal to 1, and distilling the filtrate A slurry (filtrate A will precipitate under acidic conditions) while stirring, and the distilled germanium tetrachloride is received and sealed with high-purity water. Furthermore, hydrochloric acid is added multiple times during the distillation process to ensure that the pH value of the slurry is always less than or equal to 1; the distillation temperature is 92°C-93°C, and the distillation time is 20-40 minutes.
[0031] Step 4, the filtrate A slurry after the distillation is first allowed to stand and cool and stratify, and then solid-liquid separation is performed to obtain filter residue B (mainly brown-black humic acid) and filtrate B (mainly fulvic acid); wherein, the filter residue B is washed with water multiple times, and the washing liquid is incorporated into the filtrate B.
[0032] The principle of the method of the present invention is as follows:
[0033] During the coalification process, the physical and chemical properties and structure of plant raw materials will undergo characteristic changes, but the typical structure of the original lignin is still preserved in the coal. Lignite with a lower degree of coalification has fewer condensed ring structures and more fatty chain structures. It contains more lignin-like structures and its structure is closer to the original plant residues. Lignin is a random, highly branched natural high molecular polymer with a benzene ring structure. It is composed of three basic structural units: p-hydroxyphenylpropane (H type), syringyl (S type) and guaiacyl (G type) (see Figure 2 Shown are the molecular formulas of the three basic structural units of lignin). The main connection modes between the basic structural units are α-O-4, β-O-4, β-β, β-5, β-1, 5-5, 4-O-5, etc. Among them, β-O-4 ether bond connection is the most common and important connection mode between the structural units in lignin.
[0034] Under the action of subcritical water, the CO bonds between the basic structural units of lignin are activated and hydrolyzed, and the ether bonds are broken, so that the lignin macromolecules are depolymerized into monomeric small molecules and oligomers, generating more hydrophilic groups such as hydroxyl groups and phenolic hydroxyl groups, thereby making lignin more soluble in water. Figure 3 Shown is a schematic diagram of the cleavage of the β-O-4 bond in the lignin model compound to generate a syringyl derivative.
[0035] like Figure 3 As shown in the figure, both the sodium cation and the hydroxide anion in the solution participate in the cleavage reaction of the β-O-4 bond. The sodium cation can form a cationic adduct intermediate with the negatively charged oxygen atom on the β-O-4 ether bond, reducing the bond order of the CO bond in the ether bond structure, thereby breaking the ether bond. The hydroxide anion also promotes the formation of a syringyl derivative with C=C on the side chain by removing the proton at the α-carbon atom of the β-O-4 ether bond.
[0036] like Figure 4 Shown is a schematic diagram of the cleavage of the α-O-4 bond and the formation of the guaiacol derivative. Figure 4 The reaction process shown is: due to the base (OH — ) first reacts chemically with the phenol (acidic) hydroxyl group to form a water-soluble phenol salt. Then, the phenol salt ion undergoes a structural rearrangement, which promotes the cleavage of the connection between the oxygen in the aromatic ether and the α-carbon of the phenylpropane unit, forming an intermediate (methylene quinone). The ether bond connection between two adjacent lignin structural units is completely broken, and the lignin macromolecule becomes significantly smaller.
[0037] However, during the depolymerization process, lignin will also undergo repolymerization. The main reason is that there are some highly active functional groups or active sites in the depolymerization products of lignin, which are easy to repolymerize and form macromolecules. For example, Figure 5 Shown is C αSchematic diagram of the condensation reaction of -Ar, the methylene quinone structure (intermediate degradation product) formed by the depolymerization of lignin, if the temperature and pressure are too high, C α -Ar condensation reaction, thereby increasing the molecular weight and reducing the solubility of the product in water. Adding an inhibitor that inhibits the repolymerization of the intermediate is an effective way to block the repolymerization of the intermediate degradation products of lignin, thereby achieving efficient degradation of lignin. In the present invention, phenol is used as an inhibitor, which can promote the hydrolysis and dealkylation reaction of lignin and effectively avoid the occurrence of repolymerization; it can also slow down the carbon chain scission reaction and inhibit the addition of free radicals; it can also react with the decomposition fragments derived from lignin and block their active sites to prevent crosslinking reactions and repolymerization reactions.
[0038] The present invention provides a conventional lignite alkali extraction method as a comparative example for comparison with multiple embodiments of the method of the present invention to illustrate the technical superiority of the method of the present invention.
[0039] The conventional lignite alkali extraction method is as follows:
[0040] A lignite sample, with a particle size of -0.2mm, a primary total humic acid content of 13.19%, a primary brown-black humic acid content of 7%, a primary yellow humic acid content of 6.19%, and a germanium content of 249.9g / t. The humus substances therein were alkali-dissolved with 0.3mol / LNaOH solution, with a liquid-to-solid ratio of 8:1 (mass ratio), an alkali dissolution temperature of 100°C, a reaction of 4 hours, and coal slurry filtration. The yield of the obtained filter residue A was 81.06%. The filtrate A was adjusted with hydrochloric acid solution and the pH value was maintained between 0.9-1 for distillation. The distillation temperature was 92-93°C. After distillation for 40 minutes, the germanium recovery rate of the germanium tetrachloride product was 61.27%, and the distillation residue was The mixture was allowed to stand, cool and stratify, and then filtered to obtain residue B and filtrate B with yields of 7.54% and 27.76% respectively (based on 100% mass of the coal sample). The purity of the two was determined in accordance with GB / T34766-2017 and GB / T34765-2017. Finally, the yield of brown-black humic acid in the residue B was 6.71% (based on 100% mass of the coal sample), and the yield of fulvic acid in the filtrate B was 6.17% (based on 100% mass of the coal sample).
[0041] Example 1: The same coal sample was subjected to the hydrothermal decomposition method of the present invention, under the following conditions: 0.4 mol / L NaOH solution was used as a catalyst, the liquid-to-solid ratio was 8:1, the amount of phenol added was 11% of the mass of the coal sample, the hydrothermal depolymerization temperature was 200°C, the reaction was carried out for 4 hours, and the reaction was performed after filtration to obtain a residue A with a yield of 30.67% (based on the mass of the coal sample as 100%). The filtrate A was adjusted with hydrochloric acid and the pH value was maintained between 0.9 and 1, and distilled while stirring at a distillation temperature of 92-93°C. After distillation for 40 minutes, the germanium recovery rate of the germanium tetrachloride product was 92.83%, which was 31.56% higher than that of the conventional alkali extraction method. The distillation residue was cooled and allowed to stand for stratification, and then filtered for the second time to obtain residue B and filtrate B, with yields of 35.26% and 58.44% (based on 100% coal sample mass). The purity of the two was determined in accordance with GB / T34766-2017 and GB / T34765-2017. The final yield of brown-black humic acid in residue B was 31.6% (based on 100% coal sample mass), which was 24.89% higher than that of conventional alkaline extraction. The yield of fulvic acid in filtrate B was 33.38% (based on 100% coal sample mass). Since filtrate B contained 11% of inhibitor phenol, it was calculated to be 16.21% higher than that of conventional alkaline extraction, with a significant increase.
[0042] Example 2: The same coal sample was subjected to hydrothermal decomposition under the following conditions: 0.1 mol / L NaOH solution was used as a catalyst, the liquid-to-solid ratio was 4:1, the amount of phenol added was 9% of the mass of the coal sample, the hydrothermal depolymerization temperature was 180°C, the reaction was carried out for 2 hours, and the reaction was filtered after the reaction to obtain a residue A yield of 63.37% (based on the mass of the coal sample as 100%). The filtrate A was adjusted with hydrochloric acid and the pH value was maintained between 0.9 and 1, and distilled while stirring at a distillation temperature of 92-93°C. After distillation for 20 minutes, the germanium recovery rate of the germanium tetrachloride product was 73.62%, which was 12.35% higher than that of the conventional alkali extraction method. The distillation residue was cooled and allowed to stand for stratification, and then filtered for the second time to obtain residue B and filtrate B, with yields of 15.79% and 35.9% (based on 100% coal sample mass). The purity of the two was determined in accordance with GB / T34766-2017 and GB / T34765-2017. The final yield of brown-black humic acid in residue B was 15.07% (based on 100% coal sample mass), which was 8.36% higher than that of conventional alkaline extraction. The yield of fulvic acid in filtrate B was 22.17% (based on 100% coal sample mass). Since filtrate B contained 9% of inhibitor phenol, it was 7% higher than that of conventional alkaline extraction after calculation.
[0043] Example 3: The same coal sample was subjected to hydrothermal decomposition under the following conditions: 0.2 mol / L NaOH solution was used as a catalyst, the liquid-to-solid ratio was 6:1, the amount of phenol added was 10% of the mass of the coal sample, the hydrothermal depolymerization temperature was 220°C, the reaction was carried out for 3 hours, and the reaction was filtered after the reaction to obtain a residue A yield of 43.58% (based on the mass of the coal sample as 100%). The filtrate A was adjusted with hydrochloric acid and the pH value was maintained between 0.9 and 1, and distilled while stirring at a distillation temperature of 92-93°C. After distillation for 30 minutes, the germanium recovery rate of the germanium tetrachloride product was 82.52%, which was 21.25% higher than that of the conventional alkali extraction method. The distillation residue was cooled and allowed to stand for stratification, and then filtered for the second time to obtain residue B and filtrate B, with yields of 20.17% and 45.53% (based on 100% coal sample mass). The purity of the two was determined in accordance with GB / T34766-2017 and GB / T34765-2017, and the final yield of brown-black humic acid in residue B was 19.66% (based on 100% coal sample mass), which was 12.95% higher than that of conventional alkali extraction method; the yield of fulvic acid in filtrate B was 27.68% (based on 100% coal sample mass). Since filtrate B contained 10% of inhibitor phenol, it was calculated to be 11.51% higher than that of conventional alkali extraction method.
[0044] Furthermore, the present invention uses temperature (hydrothermal depolymerization temperature), reaction time (hydrothermal depolymerization reaction time), concentration (solution concentration of the alkaline catalyst NaOH), distillation time, the amount of inhibitor phenol added (the percentage of phenol in the mass of the coal sample), and liquid-to-solid ratio (the mass ratio of the solution and the coal sample) as respective variables, and conducts experiments on the conditions of alkali-catalyzed hydrothermal decomposition of lignite.
[0045] like Figure 6 Shown is a diagram showing the experimental results of the temperature change conditions of the present invention. Figure 6 The experimental conditions are that the hydrothermal depolymerization temperature is increased from 160℃ to 220℃, the temperature is increased by 10℃ each time, the reaction time is 4h, the NaOH solution concentration is 0.3mol / L, the distillation temperature is controlled at 92℃-93℃, the distillation time is 40min, the phenol addition amount is 11%, and the liquid-solid ratio is 8:1. Figure 6 It can be seen that when other conditions are fixed, the germanium recovery rate, brown-black humic acid yield and fulvic acid yield increase with the increase of temperature between 160℃ and 200℃ for hydrothermal depolymerization, and the germanium recovery rate, brown-black humic acid yield and fulvic acid yield decrease at temperatures higher than 200℃ compared with those at 200℃.
[0046] like Figure 7 Shown is a graph showing the experimental results of the reaction time variation conditions of the present invention. Figure 7The experimental conditions are that the hydrothermal depolymerization reaction time increases from 0.5h to 5h, and the increment time of each experiment is 30min. The test is carried out under the conditions of hydrothermal depolymerization temperature of 200℃, NaOH solution concentration of 0.3mol / L, distillation temperature controlled at 92℃-93℃, distillation time of 40min, phenol addition amount of 11%, and liquid-solid ratio of 8:1. Figure 7 As shown in the figure, under other fixed conditions, the germanium recovery rate, brown-black humic acid production and fulvic acid production increase with the increase of reaction time before the reaction time of 4h. However, after the reaction time continues to increase beyond 4h, the germanium recovery rate, brown-black humic acid production and fulvic acid production decrease slightly compared with the 4h condition. After the reaction time of 2h, the germanium recovery rate, brown-black humic acid production and fulvic acid production have a line segment of obvious sharp increase until the reaction time reaches the highest point of yield at 4h, and then maintains balance and begins to decline.
[0047] like Figure 8 Shown is a graph showing the experimental results of the alkali solution concentration change conditions of the present invention. Figure 8 The experimental conditions were that the concentration of NaOH solution increased from 0.05mol / L to 0.5mol / L, and the concentration increased by 0.05mol / L each time. The experiment was carried out under the conditions of hydrothermal depolymerization temperature of 200℃, reaction time of 4h, distillation temperature controlled at 92℃-93℃, distillation time of 40min, phenol addition of 11%, and liquid-solid ratio of 8:1. Figure 8 It can be seen that under the environment where other conditions are fixed, the change of NaOH solution concentration has a significant effect on the germanium recovery rate, brown-black humic acid production and fulvic acid production. With the increase of the catalyst NaOH solution concentration, the germanium recovery rate, brown-black humic acid production and fulvic acid production will increase significantly until the NaOH solution concentration reaches the highest point at about 0.4mol / L. Under the condition of concentration higher than 0.4mol / L, the germanium recovery rate, brown-black humic acid production and fulvic acid production will not increase significantly and may even decrease. Therefore, in order to obtain the ideal yield and take into account the economic benefits, the catalyst NaOH solution concentration of 0.4mol / L is most suitable.
[0048] Fig. 9 Shown is a graph showing the results of the distillation time variation condition experiment of the present invention. Fig. 9The experimental conditions are that the distillation time increases from 5min to 50min, and the time increment for each experiment is 5min. The test is carried out under the conditions of hydrothermal depolymerization temperature of 200℃, reaction time of 4h, NaOH solution concentration of 0.4mol / L, distillation temperature controlled at 92℃-93℃, phenol addition of 11%, and liquid-solid ratio of 8:1. As can be seen from the figure, the effect of distillation time on the yield of brown-black humic acid and fulvic acid is not strong, and the distillation time is the key factor affecting the recovery rate of germanium. When the distillation time is less than 20min, the recovery rate of germanium is very low, and the recovery rate of germanium increases significantly when the distillation time continues to increase, until it reaches the highest value of 92.83% at 40min. At the same time, the yield of brown-black humic acid and fulvic acid also reaches the highest 31.6% and 33.38%. At this time, extending the distillation time will not have a significant effect.
[0049] Fig.10 Shown is a graph showing the results of an experiment on varying the amount of phenol added according to the present invention. Fig.10 The experimental conditions are that the amount of phenol added is from 8% to 13%, with an increase of 1% each time, and the test is carried out under the conditions of hydrothermal depolymerization temperature of 200℃, reaction time of 4h, concentration of 0.4mol / L, distillation temperature controlled at 92℃-93℃, distillation time of 40min, and liquid-solid ratio of 8:1. It can be seen from the figure that the addition of phenol has an effect on the germanium recovery rate, brown-black humic acid production and fulvic acid production. When the amount of phenol added accounts for 11% of the coal sample mass, the germanium recovery rate, brown-black humic acid production and fulvic acid production reach the maximum value, so when other experimental conditions remain unchanged, the phenol addition amount of 11% is the best and most economical condition.
[0050] Fig.11 Shown is a graph showing the experimental results of the liquid-to-solid ratio variation conditions of the present invention. Fig.11 The experiment shown in the figure was conducted six times with liquid-solid ratios ranging from 2:1 to 12:1. Other conditions were: hydrothermal depolymerization temperature 200°C, reaction time 4h, concentration 0.4mol / L, distillation temperature controlled at 92°C-93°C, distillation time 40min, and phenol addition 11%. It can be seen from the figure that the change in liquid-solid ratio has a great influence on the germanium recovery rate, brown-black humic acid production and fulvic acid production. When the liquid-solid ratio reaches above 6:1, the germanium recovery rate, brown-black humic acid production and fulvic acid production are significantly improved until the liquid-solid ratio reaches a peak of 8:1.
[0051] Based on the above experiments, the present invention obtains the best results under the conditions in Example 1.
[0052] The above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation methods. For those of ordinary skill in the art, other different forms of changes can be made based on the above description. And the obvious changes derived from this belong to the scope of protection of the present invention. Finally, it should be noted that the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
Claims
1. A method for extracting germanium from lignite, characterized in that it comprises: Step 1, mixing germanium-containing lignite with alkali solution, and adding an inhibitor to carry out hydrothermal decomposition reaction to obtain slurry; Step 2, performing solid-liquid separation on the slurry obtained in step 1 to obtain filter residue A and filtrate A; wherein the filter residue A is washed with water for multiple times, and the washing liquid is mixed into the filtrate A; Step 3, adjusting the pH value of the filtrate A to be less than or equal to 1 with hydrochloric acid, distilling the filtrate A slurry while stirring, and receiving and sealing the distilled germanium tetrachloride with high-purity water; Step 4, the filtrate A slurry after the distillation is first allowed to stand and cool and stratify, and then solid-liquid separation is performed to obtain filter residue B and filtrate B; wherein the filter residue B is washed with water for multiple times, and the washing liquid is incorporated into the filtrate B.
2. The method for extracting germanium from lignite according to claim 1, characterized in that: Alkali solution and germanium-containing lignite are taken at a liquid-to-solid mass ratio of 4:1-8:
1.
3. The method for extracting germanium from lignite according to claim 1, characterized in that: The alkali solution is selected from sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, potassium carbonate solution, sodium sulfide solution, or any combination thereof.
4. The method for extracting germanium from lignite according to claim 3, characterized in that: The alkali solution is sodium hydroxide solution with a concentration of 0.1mol / L-0.4mol / L.
5. The method for extracting germanium from lignite according to claim 1, characterized in that: The inhibitor is phenol or boric acid.
6. The method for extracting germanium from lignite according to claim 5, characterized in that: The inhibitor is phenol, and the added amount is 9%-11% of the mass of the germanium-containing lignite.
7. The method for extracting germanium from lignite according to claim 1, characterized in that: The hydrothermal decomposition temperature is 180°C-220°C, and the reaction time is 2-4 hours.
8. The method for extracting germanium from lignite according to claim 1, characterized in that: The distillation temperature is 92°C-93°C, and the distillation time is 20-40 minutes.
